Silica Sulfuric Acid as an Efficient Heterogeneous Catalyst for the Solvent-Free Synthesis of 1-Substituted 1H-1,2,3,4-Tetrazoles - Davood Habibi; Hiva Nabavi; Mahmoud Nasrollahzadeh (Journal of Chemistry)
Silica sulfuric acid (SSA) was found to be an efficient heterogeneous catalyst for the synthesis of 1-substituted 1H-1,2,3,4-tetrazoles from the reaction of primary amines with triethyl orthoformate and sodium azide under thermal and solvent-free conditions.